2016
DOI: 10.1016/j.it.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Helminth-Tuberculosis Co-infection: An Immunologic Perspective

Abstract: Over 2 billion people worldwide are infected with helminths (worms). Similarly, infection with Mycobacterium tuberculosis (Mtb) occurs in over a third of the world's population, often with a great degree of geographical overlap with helminth infection. Interestingly, the responses induced by the extracellular helminths and those induced by the intracellular Mtb are often mutually antagonistic and, as a consequence, can result in impaired (or cross-regulated) host responses to either of the infecting pathogens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(145 citation statements)
references
References 89 publications
5
139
0
1
Order By: Relevance
“…17 This suggests that infection susceptibility to extracellular fungi such as C. albicans is likely a result of a combination of factors rather than a deficiency of just one cytokine, a situation likely to apply as well for host resistance to intracellular pathogens such as M. tuberculosis. [19][20][21][22]61,64 In summary, the absence of TB reactivation in secukinumab clinical studies 17 (and further detailed here) is moreover supported by experimental in vitro studies showing lack of effect of secukinumab on M. tuberculosis dormancy in a human in vitro microgranuloma model (this study), and lack of compromised host resistance in anti-IL-17A-treated M. tuberculosis-infected mice. 37 Collecting real-world evidence data, through registries, will be an opportunity to further substantiate the safety of secukinumab in this regard.…”
Section: Discussionsupporting
confidence: 72%
“…17 This suggests that infection susceptibility to extracellular fungi such as C. albicans is likely a result of a combination of factors rather than a deficiency of just one cytokine, a situation likely to apply as well for host resistance to intracellular pathogens such as M. tuberculosis. [19][20][21][22]61,64 In summary, the absence of TB reactivation in secukinumab clinical studies 17 (and further detailed here) is moreover supported by experimental in vitro studies showing lack of effect of secukinumab on M. tuberculosis dormancy in a human in vitro microgranuloma model (this study), and lack of compromised host resistance in anti-IL-17A-treated M. tuberculosis-infected mice. 37 Collecting real-world evidence data, through registries, will be an opportunity to further substantiate the safety of secukinumab in this regard.…”
Section: Discussionsupporting
confidence: 72%
“…Single infection with L donovani induced expression of a mixture of type 1, type 2 and regulatory transcripts in livers, with strongest impact on type 1 genes (Figure D). iNOS and subsequent NO generation by macrophages is fundamental for control of intracellular pathogens of macrophages in mice . In line with a higher parasite burden, nos2 expression was reduced in livers of coinfected mice compared to the single L donovani ‐infected mice (Figure D,E).…”
Section: Resultsmentioning
confidence: 62%
“…It has been shown that control and susceptibility of murine Leishmania donovani infection correlate well with generation of type 1 responses or lack thereof, respectively . Notably, intestinal worm infections are most common in poor rural areas, often geographically overlapping with areas that are endemic for leishmaniasis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-infections have effects on health at multiple levels: Co-infections can increase or decrease the rate of transmission of other infections [3] , modulate the host immune response [4] , create protection and resilience or susceptibility to further infections [5,6] , alter the performance of diagnostic tests and antimicrobial chemotherapy [7,8] , and even create opportunities for the emergence of new pathogens [9,10] . In other words, some co-infections can have detrimental, or even beneficial, outcomes.…”
Section: Introductionmentioning
confidence: 99%